Instituting an inclusive built environment for the differently-abled persons thru activity-based design - Sanchez, Jeremy Roy A. (2008)
Anyone who acquires physical disability, or born with one, finds himself facing more than just adjustment to a physical impairment or long term illness that prevents him from walking as fast as other people or holding a job in competitive employment. He is regarded by others and even by himself as ?different' and his difference is considered an undesirable one, creating a sense of awkwardness, embarrassment, and and confusion on one's social interaction with others. Thus, the principles of community integration advocates for the inclusion of the differently-abled individuals to the community through active participation in the activities in the community such as recreational activities. Recreational activity is more than just a form of leisure activity. It is also regarded as a social activity which could be used when trying to established a relationship or attempting to initiate inclusion with the rest of the members of the community or to the mainstream society. Furthermore, according to studies, recreational activities could also be employed as a form of rehabilitative activity for those individuals who are experiencing underdevelopments of their motor skills especially the differently-abled persons. The process of inclusion on the other hand cannot be implemented if the immediate environment that the differently-abled wishes to be included is not designed to accommodate their condition. As revealed in this study the current condition of the recreational environment in most community is not conceived with the consideration of the condition of differently-abled in mind which, consequently further results in stigmatizing this marginalized group in or society.